The effectiveness of jigsaw learning strategy to teach speaking - Urip Widodo; Mugiyo Mugiyo (International Journal of Language Teaching and Education, 2021)
This research aims to know whether the jigsaw learning strategy is better than the audio-lingual method to teach speaking. This experimental research was carried out in the vocational school. The population was four classes (140 students) of eleventh grade A, B, C, D, and E. The samples were the eleventh grade A as the experimental group and B as the control group. Each group consists of 30 students. The experimental group was taught using the Jigsaw learning strategy, while the control group used the Audio-Lingual Method. The data collection technique was through the speaking test, and the data analysis technique was through descriptive statistics and inferential statistics. The data analysis shows that the mean score of the students who were taught by using the jigsaw learning strategy is 81,23, while the mean score of the students who were taught by using the audio-lingual method is 76,03. Moreover, the Fo (8,77) is higher than Ft (4,00) at the significance level of significance α= 0,05, which means the null hypotheses are rejected, and the alternative hypotheses are accepted. In conclusion, the jigsaw learning strategy is more effective than the audio-lingual method to teach speaking.